Suppressive effects on weeds and dry matter yields of cover crops - Ferreira, Alexandre Cunha de Barcellos; Borin, Ana Luiza Dias Coelho; Bogiani, Julio Cesar; Lamas, Fernando Mendes (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the dry matter yield of cover crops and their suppressive effects on weeds. The experiment was carried out during three years in a cerrado area of the state of Goiás, Brazil, and consisted of 16 treatments with fallow and cover crops cultivated in single cropping and intercropping. Fallow allowed high weed infestation. Cover crops affected the composition of weeds, which showed greater diversity in fallow, followed by the Pennisetum glaucum 'BRS 1501' and Cajanus cajan crops. In the average of the three experimental years, the highest dry matter yield was observed for the treatments Panicum maximum (10,857 kg ha-1), Urochloa brizantha 'Piatã' (11,437 kg ha-1), U. ruziziensis (9,463 kg ha-1), and U. ruziziensis intercropped with Crotalaria spectabilis (9,167 kg ha-1), which prevented weed infestation. Pennisetum glaucum 'BRS 1501' had a low dry matter yield (<5,000 kg ha-1) and did not suppress weeds. Panicum maximum, U. brizantha 'Piatã', U. ruziziensis, and U. ruziziensis intercropped with C. spectabilis provide high dry matter yield and suppress weed infestation in the cerrado area.